2019
DOI: 10.1016/j.ijid.2019.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Candida auris fungemia at a single facility in Kenya

Abstract: Objectives: Candida auris emerged as a human pathogen in 2009 and has subsequently been identified around the world as a cause of invasive candidiasis. We did an analysis from a single institution in order to analyze risk factors and outcomes for C. auris candidemia. Methods: Patients with candidemia were identified by the electronic medical record and reviewed for risk factors and outcome. Candida isolates were identified by Vitek2 as Candida haemulonii, but species determinations for 21 of the isolates using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
23
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 25 publications
4
23
1
2
Order By: Relevance
“…We utilized collection dates for clinical isolates and associated environmental samples, such as swabs from healthcare facilities, which ranged from 2004 to 2018; most (98%) were collected from 2012 to 2018 ( Figure 2A ). By analyzing Clade III isolates from a single healthcare facility in Kenya experiencing an outbreak of ongoing transmission (25), we confirmed that the divergence level of these isolates are temporally corelated, supporting use of molecular clock analyses, and calculated a mutation rate of 1.8695 e-5 substitutions per site per year ( Supplementary Figure 1 ). This rate was used for a Bayesian approach for molecular dating of a phylogeny for all four clades.…”
Section: Resultssupporting
confidence: 58%
“…We utilized collection dates for clinical isolates and associated environmental samples, such as swabs from healthcare facilities, which ranged from 2004 to 2018; most (98%) were collected from 2012 to 2018 ( Figure 2A ). By analyzing Clade III isolates from a single healthcare facility in Kenya experiencing an outbreak of ongoing transmission (25), we confirmed that the divergence level of these isolates are temporally corelated, supporting use of molecular clock analyses, and calculated a mutation rate of 1.8695 e-5 substitutions per site per year ( Supplementary Figure 1 ). This rate was used for a Bayesian approach for molecular dating of a phylogeny for all four clades.…”
Section: Resultssupporting
confidence: 58%
“…Exemplifying this is how common C. auris has become in some hospitals from regions with few additional reports of cases (van Schalkwyk et al, 2019). For example, in the Aga Khan University Hospital in Nairobi, Kenya between 2010 and 2016, C. auris was the most common cause of candidemia (38% of 201 patients) (Adam et al, 2019), suggesting that other hospitals in Kenya and in neighboring countries are likely to also harbor C. auris. Necessary steps to better understanding the epidemiology of C. auris will therefore include greater sampling and reporting from regions that underreported C. auris cases, a transition away from unreliable diagnostic methods, and further genomic analysis describing the population genetics of the various lineages, all of which may reveal its geospatial origin and subsequent spread.…”
Section: Genomic Epidemiology Of C Aurismentioning
confidence: 99%
“…Since then, invasive infections, especially candidemia, have increased [8]. The emergence of C. auris has changed candidemia epidemiology in certain countries, even outcompeting the most common fungal pathogen Candida albicans at a number of centers in South Africa [9][10][11][12][13]. Additionally, outbreaks continuing for months have been described, sometimes resulting in the closing of intensive care units [10,14,15].…”
Section: Clinical and Epidemiological Basis Of Diseasementioning
confidence: 99%